Seismic Assessment of First and Second Secant Stiffness for the Masonry Infilled RC Frame - Galatage, Abhijeet A.; Patil, Satish B. (Salehan Institute of Higher Education, 2025)
The seismic resilience of composite concrete frame structures composed with masonry infill walls, is a critical research area due to its impact on structural performance during earthquakes. Most studies on reinforced concrete (RC) frames focus on key seismic response parameters like lateral strength and overall hysteretic behavior under cyclic loading, often analyzing the first and second secant stiffness throughout the seismic loading process. The present study examines the first and second secant stiffness as the structural performance during earthquake. A series of experimental tests are performed on half scaled RC frames filled with autoclaved aerated concrete (AAC) block masonry with external dimensions of 1.5 m x 1.5 m. These frames are subjected to displacements ranging from 2 mm to 6 mm and frequencies between 1 Hz and 7 Hz for simulating earthquake loading conditions. The experimental program aimed to evaluate the resistance of structure to earthquake loading by using dual mode of testing viz. displacement and frequency-controlled loading protocol. During test the RC frame responded elasto-plastically due to minor cracking at block joints and localized yielding at the interface between the frame and the infill at lower frequencies and displacements. Conversely the degradation of both first and second secant stiffness values became more pronounced at higher frequencies. The first secant stiffness decreased by 73.4%, while the second secant stiffness showed increase of 24.6% at a displacement of 4 mm and a frequency of 4 Hz with respect to the previous loading cycle which indicated the complex stress redistribution and temporary stabilization. Doi: 10.28991/CEJ-2025-011-02-05 Full Text: PDF